Exploring the African Immigrant Entrepreneurship - Job Creation Nexus: A South African Case Study - Bernard Lama Ngota; Sookdhev Rajkaran; Sanjay Balkaran; Eric Ernest Mang’unyi (International Review of Management and Marketing, 2017)
Generally, the role and importance of African immigrant entrepreneurship had been rarely elaborated with perspectives to its contribution to job creation. Therefore, the aim of this paper was to assess the contributions made by African immigrant entrepreneurs’ towards employment creation in the Eastern Cape Province, South Africa. Pragmatic paradigm was adopted and mixed methods research design was selected. Data obtained for 165 entrepreneurs through questionnaire and semi-structured interviews formed the basis for the analysis. Descriptive and content analyses were used to analyse data. The results of the study revealed that immigrant small, medium and enterprises (SMEs) contribute towards employment creation, and where the majority employed is locals. Adaptive immigration policy thus requires a holistic appreciation of the African immigrants’ contributions to the economy which stimulate economic growth and new business opportunities. The research contributes to the sparse knowledge on immigrant entrepreneurship in an emerging economy setting. It provides empirical support for the theoretical relationship between African immigrant entrepreneurship and host country’s economic growth.